Hubungan Kebiasaan Menggosok Gigi dan Konsumsi Makanan Jajanan Kariogenik Dengan Kejadian Karies Gigi pada Anak Thalassemia: (Studi pada RS Kota Sukabumi) - Tri Utami (PT. Alahyan Publisher Sukabumi, 2024)
Dental caries is an infectious disease that damages the structure of the tooth, this disease causes cavities. Research Objectives: It is known the relationship between brushing habits and consumption of cariogenic snack foods with the incidence of dental caries at Sukabumi City Hospital. Research Methods: Descriptive type of analytical correlation with cross-sectional study approach. Population and Research Samples: in thalassemia children at Sukabumi City Hospital was 130 and samples were 96 people. Data on brushing habits and consumption of cariogenic snack foods with dental caries were collected using questionnaires and observation sheets. Research Results: Chi-Square statistical test results show that the p-value is 0.00 where p < 0.05 which means that there is a significant relationship between the habit of brushing teeth and the incidence of dental caries in thalassemia children at Sukabumi City Hospital and the statistical test results obtained a p-value of 0.00 where p < 0.05 which means that there is a significant relationship between the consumption of cariogenic snack foods and the incidence of dental caries in thalassemia children at Sukabumi City Hospital. Conclusion: There is a meaningful relationship between the habit of brushing teeth and the consumption of cariogenic snack foods with the incidence of dental caries in thalassemia children at Sukabumi City Hospital. Suggestion: Improving parents in attempt to motivate thalassemia children in improving health, especially oral and dental health.